Direct-Acting Antivirals Improve Access to Care and Cure for Patients With HIV and Chronic HCV Infection. (9th December 2017) - Collins, Lauren F; Chan, Austin; Zheng, Jiayin; Chow, Shein-Chung; Wilder, Julius M; Muir, Andrew J; Naggie, Susanna
Abstract: Background: Direct-acting antivirals (DAA) as curative therapy for hepatitis C virus (HCV) infection offer >95% sustained virologic response (SVR), including in patients with human immunodeficiency virus (HIV) infection. Despite improved safety and efficacy of HCV treatment, challenges remain, including drug-drug interactions between DAA and antiretroviral therapy (ART) and restrictions on access by payers. Methods: We performed a retrospective cohort study of all HIV/HCV co-infected and HCV mono-infected patients captured in care at our institution from 2011–2015, reflecting the DAA era, to determine treatment uptake and SVR, and to elucidate barriers to accessing DAA for co-infected patients. Results: We identified 9290 patients with HCV mono-infection and 507 with HIV/HCV co-infection. Compared to mono-infected patients, co-infected patients were younger and more likely to be male and African-American. For both groups, treatment uptake improved from the DAA/pegylated interferon (PEGIFN)-ribavirin to IFN-free DAA era. One-third of co-infected patients in the IFN-free DAA era required ART switch and nearly all remained virologically suppressed after 6 months. We observed SVR >95% for most patient subgroups including those with co-infection, prior treatment-experience, and cirrhosis. Predictors of access to DAA for co-infected patients included Caucasian race, CD4 count ≥200 cells/mm 3, HIV virologic suppression and cirrhosis. Time to approval of DAA was longest for patients insured by Medicaid, followed by private insurance and Medicare. Conclusions: DAA therapy has significantly improved access to HCV treatment and high SVR is independent of HIV status. However, in order to realize cure for all, barriers and disparities in access need to be urgently addressed.